Investigation of the Effect of Different Emulsifiers on the Transdermal Delivery of EGCG Entrapped in a Polymeric Micelle System - Casiraghi, Antonella; Franzè, Silvia; Selmin, Francesca; Dazio, Valeria; Minghetti, Paola (Planta Medica, 2017)
Epigallocatechin gallate, one of the most active antioxidant compounds, has a low chemical stability and ability to permeate the human epidermis. The encapsulation in polymeric micelles would be beneficial to improve both stability and permeation of epigallocatechin gallate and, therefore, to facilitate the pharmacological effects. Polymeric micelles containing epigallocatechin gallate were incorporated in O/W emulsions prepared by using different types of emulsifying systems. All emulsions were uniform in colour and aspect, without evidences of phase separation after centrifugation at the preparation time and over a 6-month period of storage at room temperature. Emulsions containing epigallocatechin gallate incorporated in polymeric micelles showed a colour variation, probably due to epigallocatechin gallate degradation, over the stability period. The skin permeability study evidenced a significant increase in epigallocatechin gallate permeation after encapsulation in micelles. Pure epigallocatechin gallate was not able to permeate the skin and only limited amounts were retained in the epidermis, while both permeated and retained amounts after 24 h were measured in the case of polymeric micelles containing epigallocatechin gallate. Moreover, the epigallocatechin gallate release and human skin permeability were affected by the type of emulsifier. The epigallocatechin gallate release in the presence of an emulsifier system based on cereal and fruit fibres never occurred. The best results in terms of release and skin permeability were obtained using glycerides of synthetic or semisynthetic origin or esters.
Keywords: antioxidant; epigallocatechin gallate; emulsifier; polymeric micelle; skin permeability